Development of an RNA Virus-Based Episomal Vector Capable of Switching Transgene Expression - Yamamoto, Yusuke; Tomonaga, Keizo; Honda, Tomoyuki (Frontiers in Microbiology, 2019)
Viral vectors are efficient gene delivery systems, although most of these vectors still present limitations to their practical use, such as achieving only transient transgene expression and a risk of insertional mutations. We have recently developed an RNA virus-based episomal vector (REVec), based on nuclear-replicating Borna disease virus (BoDV). REVec can transduce transgenes into various types of cells and stably express transgenes; however, an obstacle to the practical use of REVec is the lack of a mechanism to turn off transgene expression once REVec is transduced. Here, we developed a novel REVec system, REVec-L2b9, in which transgene expression can be switched on and off by using a theophylline-dependent self-cleaving riboswitch. Transgene expression from REVec-L2b9 was suppressed in the absence of theophylline and induced by theophylline administration. Conversely, transgene expression from REVec-L2b9 was switched off by removing theophylline. To our knowledge, REVec-L2b9 is the first nuclear-replicating RNA virus vector capable of switching transgene expression on and off as needed, which will expand the potential for gene therapies by increasing safety and usability.